Contribution of alloantigens to hepatic ischemia/reperfusion injury: Roles of natural killer cells and innate immune recognition of nonself. Issue 1 (January 2016) - Kimura, Shoko; Ozaki, Kikumi S.; Ueki, Shinya; Zhang, Matthew; Yokota, Shinichiro; Stolz, Donna B.; Geller, David A.; Murase, Noriko
Abstract : Hepatic ischemia/reperfusion injury (IRI) remains a major clinical problem and involves the innate immune system's recognition of "nonself." Considering the efficient nonself recognition by natural killer (NK) cells, we hypothesize in this study that hepatic IRI associated with liver transplantation (LT) could be augmented in allogeneic rather than in syngeneic (Syn) grafts due to alloantigen recognition by innate immune cells, especially by NK cells. Using green fluorescent protein (GFP)/Sprague‐Dawley rats, we tested our hypothesis in a rat LT model with 18 hours of cold storage in University of Wisconsin solution. Hepatic IRI was significantly augmented in allografts with higher alanine transaminase levels, increased necrosis, and vigorous proinflammatory mediator up‐regulation compared to Syn grafts. Injury increased in allografts associated with augmented GFP + host leukocyte infiltration due to significantly increased host CD11b/c + and RP‐1 + neutrophil recruitment. A large number of liver‐resident (donor) mature CD11b/c + NK cells quickly diminished from allografts, but not from Syn grafts. Depletion of mature NK cells from liver grafts with anti‐asialo monosialotetrahexosylganglioside significantly improved hepatic IRI and reduced neutrophil infiltration and proinflammatory mediators. In conclusion, early innate immune responses were more significantly enhanced in allografts than in Syn grafts during hepatic IRI, in part through NK cell recognition of "missing self." Liver Transpl 22:80‐90, 2016 . © 2015 AASLD.